Automation of Plagiarism and AI Detection in IT Students Papers with a Software Tool Using API - Oleksandr Sharyhin; Oksana Klochko; Ihor Tverdokhlib (Proceedings of the International Conference on Applied Innovations in IT, 2025)
The article considers various approaches to automating the checking of student works by lecturers for plagiarism and the presence of fragments of text/code generated by Artificial Intelligence. As a result of testing various text fragments related to IT, it was concluded that some of existing services can be considered as good candidates for plagiarism detection, but there’s no obvious choice for AI detection. Services (or combination of them) may act as a support mechanism, but final decisions should be made by lecturers. A software application has been developed to automate the routine work of lecturers of higher education institutions in checking student works for plagiarism and AI detection. Developed software application uses various APIs to search for plagiarism and fragments of text/code generated by AI. The practical value of the study lies in the possibility of using the proposed method to check student works for originality. Further research on this topic may include multi–user support, integration with existing educational platforms, adding UI components for visualization of AI/plagiarism detection results.